Kelvin force and Raman microscopies of flat SiGe structures with different compositions grown on Si(111) at high temperatures. (15th August 2018) - Shklyaev, A.A.; Bolotov, L.; Poborchii, V.; Tada, T.; Romanyuk, K.N.
Abstract: The Ge deposition on Si(111) at the very high temperature of 900 °C is accompanied by an intense Si-Ge interdiffusion and leads to the formation of three-dimensional (3D) structures, such as flat islands and lateral nanowires located on wide atomically flat (111) terraces with high atomic steps at their edges. The use of Raman spectroscopy with high spatial resolution shows that the surface areas with different 3D structures have different Ge contents from about 0.04–0.10. The Si substrate under the SiGe surface layers is weakly strained, while the substrate areas around SiGe island edges display a relatively strong compression. The areas with different Ge contents form type II heterostructures in the surface plane. The Kelvin force microscopy (KFM) data reveal that the surface potential was maximal and, hence, the Ge content was minimal in the terrace areas located near 3D SiGe structures, indicating the presence of the solid-state dewetting effect. The spatial positions of maximal KFM potentials coincide with the heterojunction positions. The results demonstrate the correlation between the Ge concentration and the KFM potential that allows mapping the composition with a high KFM spatial resolution.